2016
DOI: 10.1038/srep39488
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Hydroxylase Binding to Phospholipid Membranes Prompts Its Amyloid Aggregation and Compromises Bilayer Integrity

Abstract: Tyrosine hydroxylase (TH), a rate-limiting enzyme in the synthesis of catecholamine neurotransmitters and hormones, binds to negatively charged phospholipid membranes. Binding to both large and giant unilamellar vesicles causes membrane permeabilization, as observed by efflux and influx of fluorescence dyes. Whereas the initial protein-membrane interaction involves the N-terminal tail that constitutes an extension of the regulatory ACT-domain, prolonged membrane binding induces misfolding and self-oligomerizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 66 publications
(95 reference statements)
1
23
0
Order By: Relevance
“…Interestingly, the biosynthetic enzymes involved in catecholamine degradation, the monoamine oxidases MAO-A and MAO-B are anchored to the outer mitochondrial membrane (Binda et al, 2011). Some reports also suggest that TH may be tethered to the mitochondrial surface (Wang et al, 2009; Baumann et al, 2016), although this may be tissue specific and inducible under certain conditions; more work is needed to examine this potential functional association of mitochondria with catecholamine synthesis and degradation.…”
Section: Mitochondria Synthesize and Metabolize Glucocorticoids Anmentioning
confidence: 99%
“…Interestingly, the biosynthetic enzymes involved in catecholamine degradation, the monoamine oxidases MAO-A and MAO-B are anchored to the outer mitochondrial membrane (Binda et al, 2011). Some reports also suggest that TH may be tethered to the mitochondrial surface (Wang et al, 2009; Baumann et al, 2016), although this may be tissue specific and inducible under certain conditions; more work is needed to examine this potential functional association of mitochondria with catecholamine synthesis and degradation.…”
Section: Mitochondria Synthesize and Metabolize Glucocorticoids Anmentioning
confidence: 99%
“…The interaction of proteins with cellular membranes controls fundamental cellular processes such as membrane trafficking, cytokinesis, and intracellular signaling [1][2][3][4][5][6][7]. Beside cytoplasmic, peripheral or integral membrane proteins, there is a class of proteins known as amphitropic that interacts with lipids and membranes during their biological activity [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Proteins may also affect membrane integrity leading to cellular dysfunction or death [2,[14][15][16]. This is the case for the interaction between partially unfolded proteins/protein aggregates and lipid bilayers [17][18][19][20][21] possibly generating cytotoxicity and, in vivo, the onset and progression of several human diseases [2,4,15,16,19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dopamine, the first catechol NT at the biosynthetic pathway, is synthesized from the amino acid tyrosine in two steps: (1) the tyrosine hydroxylase converts it to L-dopa, and (2) the L-dopa decarboxylase converts it into dopamine. Although both enzymes were previously considered to be cytosolic, recent studies have indicated their association with membranes: the tyrosine hydroxylase binds to liposomes [123], and the L-dopa decarboxylase associates generally with the membranes in the cellular environment [124]. In the next step, dopamine is used as a substrate in the synthesis of two other catechol NTs: (1) norepinephrine and (2) epinephrine.…”
Section: Role Of Membranes In Intracellular Neurotransmitter Metabolismmentioning
confidence: 99%